Thermal curing kinetics of trimethylolpropane triacrylate and ethoxylated (3) trimethylolpropane triacrylate with benzoyl peroxide - Nguyen, Thanh Hung. (2012)
Thermal curing kinetics of two systems, trimethylolpropane triacrylate (TMPTA) with benzoyl peroxide (BPO), and ethoxylated (3) trimethylolpropane triacrylate (ETPTA) with benzoyl peroxide, were investigated at different ratios in weight percentage using differential scanning calorimetry. Both multi-heating rate and isothermal methods were used for the study. Activation energy was found to be lowest for the mixture consisting of TMPTA and 2%BPO. And for ETPTA system, that is the formulation with 1.5%BPO. Also, autocatalytic model was used to model successfully the non-isothermal curing process. In the case of isothermal curing, effect of temperature was considered in analyzing the kinetics. All the kinetic parameters were obtained and the validity of the kinetics models employed was thoroughly discussed.